2009
DOI: 10.1097/dcc.0b013e3181a473fe
|View full text |Cite
|
Sign up to set email alerts
|

Diabulimia

Abstract: Critical care nurses must be able to recognize the signs of symptoms of diabulimia-a potentially life-threatening disorder. Skipping insulin is used as a means of weight control in some persons with diabetes, particularly in young women. This article focuses on the assessment, pathophysiology, critical care nursing interventions, and psychosocial initiatives of interest to critical care nurses in the care of patients with diabulimia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Diabulimia is a newly defined DSED that refers to the behavior of skipping insulin doses or administering insufficient doses of insulin in order to lose weight in individuals with T1DM [ 9 ]. Insulin restriction/skipping has been shown to be the most common behavior among patients with T1DM to lose weight after self-induced vomiting, excessive exercise and laxative use [ 10 ].…”
Section: Aimmentioning
confidence: 99%
“…Diabulimia is a newly defined DSED that refers to the behavior of skipping insulin doses or administering insufficient doses of insulin in order to lose weight in individuals with T1DM [ 9 ]. Insulin restriction/skipping has been shown to be the most common behavior among patients with T1DM to lose weight after self-induced vomiting, excessive exercise and laxative use [ 10 ].…”
Section: Aimmentioning
confidence: 99%
“…These patients quickly develop diabetic ketoacidosis, one of the most serious acute complications of diabetes, as a consequence of starvation the body begins to burn fat for energy [34]. Further on, it can cause problems with the absorption of macro -and micronutrients, leading to diseases such as malnutrition, anaemia, menstrual disorders in women or other hormonal disorders [35].…”
Section: Discussionmentioning
confidence: 99%
“…Even in children and adolescents, depression has demonstrated distinct comorbidity with EDs ( Swanson et al, 2011 ), and levels of depressive symptoms have been shown to improve following weight gain in hospitalised eating disorder patients ( Sala et al, 2011 ). Depressive symptoms may also be experienced in patients engaging in IO, given that resulting hyperglycaemia is associated with low energy levels, poor sleep and trouble concentrating (( Ruth-Saad et al, 2009 ). Future research is necessary to further explore the causal relationship of depression on IO.…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…Research suggests that it may be as a method of weight loss ( Polonsky et al, 1994 ). Short-term symptoms of IO are those of hyperglycaemia: excessively high blood glucose (>11%), increased ketone levels, thirst, frequent urination, fatigue and cognitive deficits such as lack of concentration ( Ruth-Sahd et al, 2009 ). The longer and more frequent the IO, and the longer the hyperglycaemic state persists, the more severe the symptoms: weight loss, severe dehydration and increased glycosylated haemoglobin (HbA1c).…”
Section: Introductionmentioning
confidence: 99%